Pengaruh Substitusi Antibakteri Sintetik dengan Bahan Alami terhadap Daya Hambat Bakteri Penyebab Mastitis pada Sapi Perah: Studi Meta Analisis: Meta-Analysis: An Influence of Synthetic Antibacterial Substitution with Natural Material on Bacterial Growth Inhibition Caused Mastitis in Dairy Cattle - Muhammad Dimas Rachmawanto; Tri Rachmanto Prihambodo; Gian Febriza; Annisah (Jurnal Agroekoteknologi dan Agribisnis, 2023)
The aim of this study was to evaluate synthetic antibacterial agent replacement with natural antibacterial agent on the inhibition of the growth of Staphylococcus aureus and Escherichia coli. This study used a meta-analysis technique to record 128 data which collected from Google Scholar with substitution, natural material, antibacterial, and mastitis as keywords. The meta-analysis technique begins with collecting data from several scientific publications that contain data according to the specified parameter requirements and analyzed using LaunchOpenMEE. The effect of substitution of synthetic antibacterials with natural antibacterials was significant non replaceable (P<0,05) on the inhibition of mastitis cause bacteria. The conclusion from the results of this meta-analysis is that the replacement of synthetic antibacterials with natural antibacterials has not been able to optimally inhibit the ability of the bacteria that cause mastitis.